Implanting permanent left ventricular assist devices in patients on veno-arterial extracorporeal membrane oxygenation support: do we really need a cardiopulmonary bypass machine?†. (22nd March 2016) - Abdeen, Muhammad S.K.M.; Albert, Alexander; Maxhera, Bujar; Hoffmann, Till; Petrov, Georgi; Sixt, Stephan; Roussel, Elisabeth; Westenfeld, Ralf; Lichtenberg, Artur; Saeed, Diyar
Abstract: OBJECTIVES: Selected patients who failed to be weaned off temporary veno-arterial extracorporeal membrane oxygenation (VA-ECMO) support may be considered for long-term left ventricular assist devices (LVADs). Activation of the systemic inflammatory response due to the cardiopulmonary bypass (CPB) machine and its associated deleterious effects on the coagulation system have been well documented. The aim of the study was to compare the outcome of patients receiving VAD on VA-ECMO with patients who were converted to CPB at the time of VAD implantation. METHODS: Data of patients undergoing LVAD implantation between January 2010 and September 2015 were retrospectively reviewed. Inclusion criteria were patients with prior VA-ECMO. Perioperative characteristics and postoperative outcome of patients who received LVAD after VA-ECMO with (CPB group) or without CPB (no-CPB group) were compared. RESULTS: A total of 110 permanent VADs were implanted during this time frame. Forty patients had VA-ECMO prior to VAD implantation and met the inclusion criteria. The CPB was used in 23 patients and 17 patients received VAD on VA-ECMO without using CPB. The preoperative characteristics of the patients were comparable except for lower body mass index, higher international normalized ratio (INR) and higher rate of preoperative intra-aortic balloon pump usage in the CPB group ( P = 0.035, 0.008 and 0.003, respectively). The incidence of postoperative right VAD implantation and survival rate was comparable between both groups. However, the chest tube blood loss and amount of blood product usage was higher in the CPB group. The total blood loss in the first 24 h after surgery (2469 ± 2067 vs 1080 ± 941 ml, P = 0.05) and number of units of intraoperative fresh frozen plasma administered (4 ± 3 vs 1 ± 2, P = 0.02) remained higher in the CPB group even after adjustment for differences in preoperative INR value by propensity score matching. CONCLUSIONS: This study demonstrates that the CPB machine can be safely omitted when a long-term VAD is implanted on VA-ECMO support. Blood loss in the first 24 h after surgery was less and a significantly lower number of blood products were necessary in these patients compared with patients in whom the CPB machine was used. However, similar survival rates between these two groups were observed.